Physicochemical and bioactive properties of selected white yam (Dioscorea rotundata) varieties adapted to riverine areas of Nigeria - Alamu, Emmanuel Oladeji; Maziya-Dixon, B.B.; Okonkwo, C.C.; Asiedu, Robert (Academic Journals, 2014)
Yam (Dioscorea spp.) is a major food of cultural, economic and nutritional importance in Nigeria and throughout West Africa. In this sub-region, white yam (Dioscorea rotundata) is the most dominant and important species. This study is aimed at characterizing high yielding yam varieties of this species adapted to riverine areas and forest zones of Nigeria for physical and chemical characteristics. Eleven yam varieties collected from local farmers in the South-southern part of Nigeria were evaluated for their physicochemical characteristics, bioactive compounds (vitamin C, phytic acid and tannin), functional and pasting properties. Results indicated that there were significant varietal difference (P<0.05) among the parameters evaluated. The moisture contents of the investigated varieties ranged from 59.5 to 68.8%, ash content ranged from 1.39 to 2.93%, protein content from 1.96 to 4.90%, fat content from 0.356 to 3.39%, total free sugars from 1.05 to 7.02% and total starch from 33.9 to 75.7%. The bioactive content results show that vitamin C content ranged from 5.64 mg/100 g to 6.99 mg/100 g, phytate from 1.12 to 2.37% and tannin from 0.359 to 1.18 mg/g. The pasting properties results show that peak viscosity ranged from 215 to 470 RVU, trough viscosity from 198 to 385 RVU, breakdown viscosity from 8.71 to 84.5 RVU, final viscosity from 278 to 571 RVU, setback viscosity from 66.2 to 204 RVU; peak time ranged from 4.97 to 7.0 min and the pasting temperature from 61.7 to 62.6oC. This study shows that the physical and chemical characteristics of these high yield yam varieties were similar to those reported for most yam varieties in other parts of Nigeria and has a great potential as source of bioactive compounds and protein.